Incidence, severity and perceived susceptibility of COVID-19 in the UK CrossFit population - Athalie Redwood-Brown; Grant William Ralston; Jennifer Wilson (BMC, 2021)
Abstract Background Contemporary literature indicates that a higher body mass index (BMI) serves as a risk factor for metabolic disease and is also correlated with greater disease severity. Subsequently, it has been linked to increased COVID-19 severity. The purpose of the study was to investigate whether regular CrossFit™ participation was associated with lower BMI, decreased COVID-19 severity and susceptibility. Methods A cross-sectional study was conducted on 1806 CrossFit™ (CF) participants. Participants were asked about their age (yrs), sex (male vs. female), ethnic group, body height (cm) and weight (kg). Body mass index (BMI, kg/m2) was computed and consistent with WHO (2018) criteria. Participants self-reported their training history, health and lifestyle history, nutritional customs, present training status and suspected levels of exposure to COVID-19. Once submitted the collected data were coded, cleaned and analysed. Results The final model comprised of 1806 CF individuals from an online survey response rate of 2086. The participants age ranged from 18 to 65+ yrs. Self-reported mean body mass index (BMI: kg/m2) reported that < 1% were underweight, 41% were healthy, 46% overweight, 10% class I obese, 2% class II obese, and < 1% class III obese. A Kruskal-Wallis H test compared gender and self-reported probability of being infected with COVID-19 with significant differences between subgroups (x2 (4, N = 1739) = 10.86, p = 0.03). Analysis of BMI and perceived severity of COVID-19 revealed a difference however not, significant (x2 (4, N = 1739) = 9.46, p = 0.051). Results on BMI and perceived probability of COVID-19 infection revealed no significant difference (x2 (4, N = 1739) = 2.68, p = 0.61). A separate analysis on BMI and perceived COVID-19 susceptibility revealed no significant difference (x2 (4, N = 1740) = 6.02, p = 0.20). Conclusions The purpose of the study was to establish whether habitual CrossFit™ participation is associated with reduced BMI, and to further investigate whether habitual participation impacted perceptions of disease. Results of the study indicate that self-reported CrossFit™ participation during the first UK lockdown, measured in minutes of exercise was indicative of a lower BMI. This has been associated with greater host immunity to disease. A history of CrossFit™ participation was not shown to impact perceptions of disease. However, our sample population reported few changes to habitual exercise during lockdown which may be due to the 'community' and increased adherence associated with CrossFit™.